2022
DOI: 10.3390/cancers14122922
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cross-Combinations of Feature Selection and Machine-Learning Classification Methods Based on [18F]F-FDG PET/CT Radiomic Features for Metabolic Response Prediction of Metastatic Breast Cancer Lesions

Abstract: Background: This study aimed to identify optimal combinations between feature selection methods and machine-learning classifiers for predicting the metabolic response of individual metastatic breast cancer lesions, based on clinical variables and radiomic features extracted from pretreatment [18F]F-FDG PET/CT images. Methods: A total of 48 patients with confirmed metastatic breast cancer, who received different treatments, were included. All patients had an [18F]F-FDG PET/CT scan before and after the treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 46 publications
(61 reference statements)
0
10
0
Order By: Relevance
“…The cross-combination strategy could filter down irrelevant features and select the optimal ML model for classification [ 39 , 40 ]. Regarding feature selection methods, our study showed that the RFE method exhibited high performance when combined with all classifiers in building baseline ML models.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The cross-combination strategy could filter down irrelevant features and select the optimal ML model for classification [ 39 , 40 ]. Regarding feature selection methods, our study showed that the RFE method exhibited high performance when combined with all classifiers in building baseline ML models.…”
Section: Discussionmentioning
confidence: 99%
“…To find good performance baseline ML models, we used the cross-combination strategy in which each feature selection method mentioned above was combined with several classifiers [ 39 , 40 ]. We investigated six classification algorithms: support vector machine (SVM), Logistic Regression (LR), k-nearest neighbors (KNN), random forest (RF), linear discriminative analysis (LDA), and Gaussian Naïve Bayes (GBN), which were commonly used in machine learning of MRI data [ 41 , 42 , 43 , 44 , 45 ].…”
Section: Methodsmentioning
confidence: 99%
“…[45,[83][84][85][86][87] The application of ML algorithms, including but not limited to random forest (RF), support vector machine (SVM), Gaussian naive Bayes (GNB), artificial neural network (ANN), KNN, adaptive boosting (AdaBoost), logistic regression, K-means clustering, principal component analysis (PCA), and hierarchical clustering, has demonstrated potential to enhance both predictive and diagnostic accuracy. [87][88][89][90] The RF algorithm generates an ensemble of decision trees, collectively known as a forest, which can effectively tackle classification or regression tasks. Additionally, an internal optimization technique is utilized to determine an importance score for each feature, reflecting their respective contributions to the optimization process.…”
Section: Model Building and Validationmentioning
confidence: 99%
“…[ 45,83–87 ] The application of ML algorithms, including but not limited to random forest (RF), support vector machine (SVM), Gaussian naive Bayes (GNB), artificial neural network (ANN), KNN, adaptive boosting (AdaBoost), logistic regression, K ‐means clustering, principal component analysis (PCA), and hierarchical clustering, has demonstrated potential to enhance both predictive and diagnostic accuracy. [ 87–90 ]…”
Section: Radiomics Workflowmentioning
confidence: 99%
“…Recently, the value of PET/CT-based HRFs in predicting EGFR mutation status, EGFR subtypes and prognosis had been well demonstrated ( 12 18 ), which involved different feature selection methods and machine learning algorithms. These different radiomics pipelines may lead to various predictive performance ( 19 ). Feature selection methods also have a great influence on clinical predictive models ( 20 ).…”
Section: Introductionmentioning
confidence: 99%